2022
DOI: 10.3390/antibiotics11111636
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and Cell-Penetrating Peptides: Understanding Penetration for the Design of Novel Conjugate Antibiotics

Abstract: Antimicrobial peptides (AMPs) are short oligopeptides that can penetrate the bacterial inner and outer membranes. Together with cell-penetrating peptides (CPPs), they are called membrane active peptides; peptides which can translocate across biological membranes. Over the last fifty years, attempts have been made to understand the molecular features that drive the interactions of membranes with membrane active peptides. This review examines the features of a membrane these peptides exploit for translocation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 166 publications
0
9
0
Order By: Relevance
“…The membrane permeabilization activity of KLH 2 was more acute, while the permeabilization of the other two peptides was milder and more consistent. This may be due to the fact that it takes longer for the hydrophobic driving force to push the bulky aromatic ring from F or W into the membrane core compared with the aliphatic side chain from L. 60,61 In the inner membrane permeability assay, we failed to observe a dose-dependent effect throughout the monitoring period. One reason for this may be that under higher concentrations (>4 μM), the permeabilizing effect of peptides was acute.…”
Section: Discussionmentioning
confidence: 99%
“…The membrane permeabilization activity of KLH 2 was more acute, while the permeabilization of the other two peptides was milder and more consistent. This may be due to the fact that it takes longer for the hydrophobic driving force to push the bulky aromatic ring from F or W into the membrane core compared with the aliphatic side chain from L. 60,61 In the inner membrane permeability assay, we failed to observe a dose-dependent effect throughout the monitoring period. One reason for this may be that under higher concentrations (>4 μM), the permeabilizing effect of peptides was acute.…”
Section: Discussionmentioning
confidence: 99%
“…These observations clearly showed the effect of differences in the lipid compositions of bacterial membranes on the activity of AMPs and reinforce the importance of taking these differences into account when designing these peptides. 163 Indeed, it has been recently suggested that when designing AMPs, other often neglected factors, such as site of action pH should also be considered; 164,165 changes in pH have been shown to both enhance and attenuate the response of S. aureus and P. aeruginosa to the action of AMPs. 38,39,76 The Lys-PG mediated mechanisms shown here to protect S. aureus to the action of M5-NH 2 most probably involve the use of an intrinsic resistance mechanism frequently reported in studies on the susceptibility of the organism to AMPs.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of exciting reviews about the structures, activities, and mechanisms of action of CPPs and AMPs [ 28 , 29 , 30 ] are available. Some suggested reviews on the biological activity of AMPs against cancer cells [ 31 , 32 , 33 ] and CPPs as delivery systems [ 34 , 35 , 36 , 37 ] could be of interest.…”
Section: Cell-penetrating and Antimicrobial Peptides: The Basicsmentioning
confidence: 99%
“…In the current scientific literature, cumulative data about cell-penetrating antimicrobial peptides (CPAPs) with anti-infective activities to treat infections caused by obligatory or facultative intracellular pathogens are accessible. This particular class of bioactive peptides is also called antimicrobial and cell-penetrating peptides (ACPPs) [ 37 ]. Antimicrobial peptides that penetrate the target cells without causing membrane disruption exert their biocide effects intracellularly figure in the subset of CPAPs [ 38 , 39 ].…”
Section: Peptides With Cell-penetrating and Anti-infective Activity A...mentioning
confidence: 99%